Tổng hợp, cấu trúc và từ tính của vật liệu nano CoFe2O4 bằng phương pháp đồng kết tủa - Tiến, Nguyễn Anh; Tuyết, Hoàng Thị (Vietnam Journal of Chemistry, 2015)
CoFe2O4 spinel nanomaterial has been synthesized by coprecipitation method through the hydrolysis of Co(II) and Fe(III) cations in boiling water. The results of DTA/TGA/DrTGA, XRD, TEM methods showed that CoFe2O4 crystals formed after a calcinations at 700 ºC exhibited structure of cubic with the particles size of 30-50 nm, Hc = 1526.89 Oe, Ms = 41.703 emu/g, Mr = 19.545 emu/g